Pengaruh Modal Usaha, Tingkat Pendidikan, dan Pengalaman Usaha terhadap Pendapatan UMKM di Taman Vatungguni, Kota Palu - Silvana; Syamsul; Irma (Indonesian Accounting Literacy Journal, 2024)
This research aims to analyze the influence of business capital, education level and business experience on MSME income. This type of research is quantitative research. The population and sample of this research are MSME actors in Vatunguni Park, Palu City. This research data is primary data sourced from distributing questionnaires to research respondents. The data obtained was then analyzed using multiple linear regression analysis techniques. The test results show that business capital and business experience have a positive and significant effect on MSME income in Vatunguni Park, Palu City. Meanwhile, the level of education does not have a significant effect on the income of MSMEs in Vatunguni Park, Palu City.